The Gold Standard: A Qualitative Framing Analysis of Newspaper Coverage of Golden Rice in the United States and Philippines - Taylor K. Ruth; Joy N Rumble (Journal of International Agricultural and Extension Education, 2016)
Vitamin A deficiency (VAD) is a major issue in developing countries and affects approximately 250 million children, and blinding 500,000 a year. A proposed intervention to VAD is Golden Rice, a rice that has been genetically modified (GM) to contain beta-carotene, the precursor to Vitamin A. However, Golden Rice is often associated with negatively perceived GM food. Because the media is the most trusted source in providing food-risk related information, a framing analysis of Golden Rice in United States and Philippine newspapers was conducted to determine past and current frames used to describe the rice. Understanding such frames could help domestic and international extension workers develop effective communication strategies and educational opportunities. In the United States, GM food was typically the main topic, and Golden Rice was used as a supporting argument. Science and humanitarian frames were used to describe the rice in the U.S. articles. Golden Rice was more often the main topic in the Philippine articles, and more frames were identified: human health, science, policy, risk, and conflict. Golden Rice appears to be in the emergence phase of the framing cycle in the U.S. and in the conflict/resolution phase in the Philippines. Extension in the U.S. and the Philippines should provide education toolkits to journalists about Golden Rice and consider providing press releases to shape the frames used by the media. Extension workers in the Philippines should educate consumers and farmers about the science of Golden Rice to help them create informed opinions toward the product
Keywords: Golden Rice; Genetically Modified Food; Framing; Newspapers; United States; Philippines